Pynchon's Sound of Music - Hänggi, Christian (DIAPHANES, 2020)
Pynchon's Sound of Music is dedicated to cataloging, exploring, and interpreting the manifold manifestations of music in Thomas Pynchon's work. An original mix of close and distant readings, this monograph em-ploys a variety of disciplines-from literary studies and musicology to philosophy, media theory, and his-tory-to explain Pynchon through music and music through Pynchon. Encyclopedic and eclectic-though never exhaustive-in its approach, Pynchon's Sound of Music discusses the author's use of instruments such as the kazoo, the harmonica, or the saxophone and embarks on close readings of the most salient and musicologically tantalizing passages. Zooming out to a bird's eye view, all his historical musical references and allusions are put into perspective to trace the trends and tendencies in the development of the oeuvre's interest in music. A treasure trove for fans and an invaluable source for future scholarship, this book includes the Pynchon Playlist, a 900+ item catalog of all musical references, and an exhaustive index of more than 700 appear-ances of musical instruments.